Synthesis of an ABC Type Triblock Copolymer on MWCNT Surface: Structural, Thermal, Electrical and SEM Characterization - Coşkun, Mehmet; Yılmaz, Serpil (Tayfun UYGUNOĞLU, 2017)
Multi-walled carbon nanotubes (MWNTs) attached to ethylene glycol (MWNT-OH) were grafted with ring-opening polymerization of ?-caprolactone (MWNT-pCL). Initiating sites for atom transfer radical polymerization (ATRP) were formed by end acylation of MWNT-pCLwith  ?-bromopropionyl bromide. After styrene was polymerized by ATRP on the surface of the macroinitiator (MWNT-pCL-Br) in presence of CuBr/2,2?-bipyridine as catalyst at 110 oC, the triblock copolymer (MWNT-pCL-b-PS-b-pGMA) was prepared by the aid of the same technique using glycidyl methacrylate as monomer, at the same catalyst and temperature conditions, by using the diblock copolymer (MWNT-pCL-b-PS) as macroinitiator. The 1HNMR studies show that structure in terms of mer number per molecule of the ABC type triblock copolymer is MWNT-p(CL)6-b-P(S)36-b-p(GMA)1080. The determination of chemical structure of the triblock copolymer was carried out using Fourier transform infrared (FT-IR), proton nuclear magnetic resonance (1H NMR) and scanning electron microscopy (SEM). Thermal properties were investigated by using thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC). The Tg value estimated from the temperature dependence of the dielectric constant, the dielectric loss factor, and the ac conductivity for the triblock copolymer, is in agreement with the DSC value. The results of the dielectric constant and ac conductivity of the triblock copolymer were also discussed.

Etilen glikol bağlı (MWNT-OH) çok-duvarlı karbon nanotüp (MWNTs) ?-kaprolaktonun halka açılması polimerizasyonuyla aşılandı (MWNT-pCL). Atom transfer radikal polimerizasyonu (ATRP) için başlatma ucu, MWNT-pCL´nun ?-bromopropiyonil bromür ile uç açillemesiyle hazırlandı. Katalizör olarak CuBr/2,2´-bipridin yanında 110 oC de makrobaşlatıcının (MWNT-pCL-Br) yüzeyinde ATRP ile stirenin polimerizasyonundan sonra, aynı sıcaklıkta aynı katalizör yanında glisidil metakrilatın makrobaşlatıcı olarak iki bloklu kopolimer (MWNT-pCL-b-PS) kullanılarak yapılan ATRP polimerizasyonuyla üç bloklu kopolimer (MWNT-pCL-b-PS-bpGMA) hazırlandı. 1HNMR çalışmaları ABC tipi üç bloklu kopolimerin molekül başına mer sayılarının MWNT-p(CL)6-b-P(S)36-b-p(GMA)1080 şeklinde olduğu belirlendi. Üç bloklu kopolimerin kimyasal yapısının belirlenmesi Fourier dönüşümlü infrared (FT-IR), proton nükleer manyetik rezonans (1H NMR) ve taramalı electron mikroskopuyla (SEM) gerçekleştirildi. Termal özellikler termogravimetrik analiz (TGA) ve diferesiyel taramalı kalorimetre (DSC) ile incelendi. Üç bloklu kopolimerin dielektrik sabiti, dielektrik kayıp faktörü ve ac iletkenliğinin sıcaklık bağımlılığndan tahmin edilen Tg değerinin DSC den bulunan değerle uyuştuğu görüldü. Üç bloklo kopolimerin dielektrik sabiti ve ac iletkenliği de ayrıca tartışıldı.
MWCNT Yüzeyinde bir ABC Tipi Üç Bloklu Kopolimer Sentezi : Yapısal, Termal, Elektriksel ve SEM Karakterizasyonu
Keywords: Engineering; Mühendislik